GOOD NURSING PRACTICES IN ASSISTANCE TO PATIENTS WITH CHEST DRAINAGE - Ferreira Barros , Andressa; Alves Ribeiro, Wanderson; Christiny, Larissa; Campolino Sobral, Andressa; Alhan de Oliveira, Giovanna; Mello Araujo, Camilla; Maria Ferreira Guedes , Miriam; de Paula, Enimar; Silva Lima, Daiana; de Castro, Kemely; Oscar Lopes Salvati, Pedro (Health and Society, 2022)
This is a bibliographic research with a qualitative approach that aimed to describe good nursing practices in patient care with chest drain. Surgical intervention is characterized as an invasive procedure, which can cause trauma. The surgical wound is characterized by sutur-ing the edges of the tissue from a deep, mechanical and intentional incision. Due to its com-plexity, in many cases there is a need for devices that assist in the exit of liquids and gases from this process. In these cases, the use of the drain that is inserted during the procedure becomes effective and its handling is under the responsibility of the nursing team, which needs to use good practices, in view of the patient’s needs. Data were collected in a virtual database. For this purpose, the VHL was used, in the following information base: LILACS; BDENF and Google Scholar from January to February 2022. For sample selection, there was a time frame from 2017 to 2021. After associating all descriptors, 80 articles were found, 66 were excluded and 14 articles were selected. After the reflective reading, two categories emerged: Complications related to the chest tube and Nursing Care with the chest tube. It was concluded that assistance is of fundamental importance, since the nursing professional works in all periods of care from the preoperative, intraoperative and postoperative periods. Thus, nursing professionals working in this area must be in constant professional updating, have good knowledge of the processes involved in performing the chest drainage technique and ventilatory mechanics, providing quality care and preventing the emergence of diseases.